RETROSPECTIVE STUDY ON TRILOSTANE TITRATION DOSE TREATMENT IN DOGS WITH TERMINAL STAGE OF HYPERADRENOCORTICISM - Irena Celeska; Martin Nikolovski; Todor Novakov; Anastasija Angelovska; Ivica Gjurovski; Elena Atanaskova Petrov (Macedonian Veterinary Review, 2024)
Hyperadrenocorticism (HAC) in dogs is routinely treated with trilostane single-dose (CTG) which is reported to cause adverse reactions. The current retrospective study of several dogs with terminal stage of HAC aimed to compare the clinical, hematological, and biochemical effects of trilostane titration-dose treatment (TTG) with the single-dose treatment (CTG). All clinical cases (n=7) were confirmed on HAC by anamnestic, clinical, hematology, biochemistry, and low-dose dexamethasone suppression test findings, indicative for Cushing’s disease. Two cases were treated with CTG (2.2-6.7 mg/kg, single dose daily) and their treatment was discontinued on the second week due to adverse reactions. The TTG cases were treated for up to 12 weeks (0.5 mg/kg once daily for 7 days, and then with 0.5 mg/kg twice daily for 7 days). Blood samples and clinical checks were performed on 0., 4., and 12. weeks of the treatment. Hemoglobin was non-significantly higher in TTG at 12 weeks. Alanine transaminase was significantly lower in the TTG cases on the 12. week of the treatment (78.04±15.37 U/L) compared to the 0-week (137.81±24.03 U/L), and 4-week samples (131.92±23.36 U/L). No significant differences were observed with the CTG cases. Alkaline phosphatase was significantly lower on 12-week samples in TTG (251.02±93.06) compared to the 4-week (567.94±283.93 U/L), and 0-week samples (1,341.84 U/L). In conclusion, TTG has indicated to have significantly higher tendency to decrease alanine transaminase and alkaline phosphatase, alleviating the negative effects on the liver. The clinical findings were more adverse for the CTG.
Keywords: Cushing’s disease; dogs; trilostane